Surgical corrections of endovascular aneurysms: Repair complications - Utikal, Petr; Koecher, Martin; Koutna, Jirina; Bachleda, Petr; Drac, Petr; Cerna, Marie; Herman, J. (Biomedical papers, 2006)
The authors describe their experience with the use of 21 open surgical corrections after endovascular abdominal aneurysm repair, reporting the frequency, type and outcome of these procedures in their group of 165 patients treated during a 10-year period.
Keywords: Aorta/Aneurysms/Repair/Endovascular/Complications/Corrections/Additional procedures/Adjuvant procedures/